Application of the HTA Core Model for complex evaluation of the effectiveness and quality of Radium-223 treatment in patients with metastatic castration resistant prostate cancer - Beata Kiselova Bilekova; Beata Gavurova; Vladimír Rogalewicz (Health Economics Review, 2018)
Background: Health technology assessment (HTA) is currently one of the major challenges in assessing medical innovations and healthcare systems. In Europe, the European Network for Health Technology Assessment (EUnetHTA) has been aspiring to develop and implement standards for international sharing of HTA results and studies. Slovakia and many other EU countries do not have an established HTA system yet. This paper is focused on an exact description of the EUnetHTA Core Model individual domains applied to the process of selecting patients in the terminal stage of prostate cancer for Radium-223 treatment under particular conditions of the Institute of Nuclear and Molecular Medicine (INMM) in Koésice, Slovakia. Results: We produced the first pilot HTA report using the HTA Core Model in Slovakia. The main objective was to collect all relevant information on the particular technology, and provide its summary to the interested stakeholders on one spot. Rather than applying detailed individual items, i.e. assessment elements and assessment element cards, we concentrated on the content of individual domains and tried to fill them with the best country, facility and intervention related data. The dataset consisted of 52 patients that finished the treatment in the period 2015-2017. The patients were carefully selected according to the Radium-223 producer's criteria. Only 33 patients received the full therapy consisting of six applications; their average survival was 10.5 months from the application of the last dose. Conclusions: Based on the results of our analyzes, we recommended several changes to the INMM processes and patient follow-up checks during the treatment process in order to make the therapy more effective. The greatest benefit is expected after the implementation of a 68Ge/68Ga generator in 2018, as the selection of patients suitable for the Radium-223 treatment will improve. We showed that the HTA Core Model can be implemented in Slovakia, even under conditions of no formal HTA support or institutionalization.
Keywords: 330; Metastatic castration-resistant prostate cancer; Health technology assessment; HTA; HTA Core Model; Health technologies and interventions